Prevalence of astigmatism in school going children: a hospital-based study at Majeedia Hospital, New Delhi - Ali, Jamshed; Kumari, Ragni; Dubey, Gaurav; Afroz, Simi; Gupta, Sunil Kumar; Srivastava, Namrata; Sharma, Pratik; Kumar, Vibha (International Journal Of Community Medicine And Public Health, 2022)
Background: Generally, astigmatism is type of refractive error due to distorted and irregular of the cornea. It’s generally related to the cornea and lens. Methods: This is cross-sectional study conducted over a period from January 2017 till April 2017 among the patients in HAHC hospital. A comprehensive eye examination was used to analyse the refractive error (astigmatism). And the research was approved by the institutional review board and the ethics committee for at department of paramedical sciences, Jamia Hamdard New Delhi India. Results: A total of 90 patients were included in the study. Out of which 37 were boys and 52 were girls. The rate of myopic astigmatism increased with age. In contrast, the rate of hyperopic and mixed astigmatism decreased with age. In addition, the rate of with-the-rule astigmatism increased and the rate of against-the-rule decreased with respect to age, but oblique astigmatism was rather stable with age. Conclusions: There was more myopic astigmatism and with-the-rule astigmatism in total of 90 patients. Our hospital-based study shows there are high percentage of astigmatism (47.8%) in school aged children in south Delhi region. It is important to study in future, to further evaluate the causes and magnitude of astigmatism and increase awareness among school going children in South Delhi.